Dos nuevas especies de Croton (Euphorbiaceae) en el Neotrópico - González Ramírez, José; Poveda Álvarez, Luis (Lankesteriana: International Journal on Orchidology, 2016)
Two new species of Croton L. (Euphorbiaceae) restricted to Costa Rica are described and illus- trated in this paper: Croton corinthius from the lowlands of the Caribbean slope and Croton megistocarpus from the midlands of both slopes of the main ridges. The first is distinguished for the presence of stalked glands near the vein axils of the leaves. The second is compared to C. pachypodus Webster, from Panama and Colombia.